2021
DOI: 10.3390/polym13162636
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Flooding in Heterogeneous Heavy Oil Reservoirs: Experimental and Simulation Studies

Abstract: Polymer flooding (PF) in heterogeneous heavy oil reservoirs is not only closely related to polymer degradation, but also to non-Newtonian flow. In this paper, both experimental and simulation methods are combined to investigate this type of flooding. Through experiments, the degradation of polymer, rheological properties of fluids, and flow of fluids in porous media were determined. Based on the experimental results, a novel mathematical model was established, and a new PF simulator was designed, validated, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…To determine applicable areas for polymer flooding, permeability variation is used instead of absolute permeability. It was determined that heterogeneous reservoirs are the best candidates for polymer flooding for several reasons, such as [ 86 , 87 ] the reduction in the rock’s permeability caused by polymer solutions and the tendency of the solution to flow in the direction of unswept reservoir areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine applicable areas for polymer flooding, permeability variation is used instead of absolute permeability. It was determined that heterogeneous reservoirs are the best candidates for polymer flooding for several reasons, such as [ 86 , 87 ] the reduction in the rock’s permeability caused by polymer solutions and the tendency of the solution to flow in the direction of unswept reservoir areas.…”
Section: Discussionmentioning
confidence: 99%
“…Several polymer flooding projects and experiments have been implemented worldwide in order to increase oil recovery and reduce water production through mobility control [ 86 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ]. A summary of some field studies conducted in different countries worldwide using polymer flooding is provided in Table 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that with the increase in polymer molecular weight, the oil displacement efficiency of the high-permeability model increased, and that of the low-permeability model first increased and then decreased [22]. Xin et al demonstrated that the critical pressure gradient of heavy oil is higher in the low-permeability porous media than in the high-permeability porous media during polymer flooding in heterogeneous heavy oil reservoirs using polymer flooding experiments and simulations [23]. Zhong et al developed a solver based on the OpenFOAM platform considering the interlayer heterogeneity; the simulation indicated that the reservoir structure has more severe heterogeneity and worse connectivity, its oil displacement efficiency is relatively low, and the commingled production has a stronger effect on the micro-oil displacement efficiency of a poorer pore structure layer than that of a better pore structure layer [24].…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is supposed to not be suitable for many engineering flows in which the fluids can possess rheologically complex properties such as shear-dependence, yield stress, viscoelasticity, or thixotropy. Examples of non-Newtonian materials can range from mineral suspensions [9,10], clay suspensions [11,12], and lava [13,14] to crude oil [15][16][17], melting metal [18,19], printing ink [20,21], painting [22], polymer [23][24][25][26][27][28], or even human blood [29,30]. To deal with the lid-driven cavity flow problem of these fluids, computational approaches were mainly adopted in previous works.…”
Section: Introductionmentioning
confidence: 99%